Big sky - Guthrie, A B (Franklin Watts New York, 1947)
The first in an epic western saga that spans over a hundred years in the course of six novels. Boone Caudill travels west to the Rockies, leaving his abusive father to find a life of freedom in the wild. He wins the love of a beautiful Blackfoot princess, a woman willing to love him despite his wild ways. Their lives become forever entwined through adventure, travel, and eventually betrayal. He finds that freedom comes at a price, higher than he ever could have imagined.
41689
Keywords: Frontier and Pioneer Life -- Fiction -- Montana; Siksika Indians -- Fiction; Montana -- History -- Fiction -- 19th Century